Synthesis, Characterization, and Thermal Decomposition Kinetics of Manganese Complex of Methionine Hydroxy Analogue - Mei-Ling Wang; Zhi-Xian Wu; Qing Zang; Guo-Qing Zhong (International Journal of Chemical Engineering)
The manganese complex of methionine hydroxy analogue was synthesized with methionine hydroxy analogue and manganese chloride as main raw materials. The composition and structure of the complex were characterized by elemental analyses, infrared spectra, and X-ray powder diffraction. The formula of the complex was Mn(C5H9O3S)2. The experimental results indicated that the manganese ion was, respectively, coordinated by the carboxylic and hydroxyl oxygen atoms from the methionine hydroxy analogue ligand. The crystal structure of the complex belonged to monoclinic system with the lattice parameters of a = 1.2775 nm, b = 1.5764 nm, c = 1.5764 nm, and β = 94.06°. The thermal decomposition process of the complex was studied by thermogravimetry and differential thermal analysis. The decomposition of the complex has taken place above 200°C. The residue was mainly manganese sulfide, and the experimental and calculated percentage mass loss was also given. The parameters of thermal decomposition kinetics for the complex, such as activation energy, reaction order, and preexponential factor, were calculated by using Kissinger, Flynn-Wall-Ozawa, and Freeman-Carroll methods, and the kinetic equations of the thermal decomposition were obtained.